(untitled) (Research, Society and Development, 2022)
The Psychosocial Care Network (RAPS) is a thematic health network, which aims to ensure that people with mental disorders and needs arising from drug use have access to comprehensive and humanized care, based on the articulation of services in the various points of care of the Unified Health System. The objective of this work is to perform a statistical and mathematical analysis of the data of hospitalizations for mental and behavioral disorders of the municipalities under the jurisdiction of the Regional Superintendence of Health (SRS) of Teófilo Otoni /MG, aiming to fill the care gaps and expand the coverage of care in RAPS. This is bibliographic research developed based on material published in books; scientific journals; official websites of the Ministry of Health and the State Health Secretariat of Minas Gerais (MG). The results showed that the average number of hospital admissions by CAPS I, presents 14 hospitalizations per year, for every 1000 inhabitants, this value is three times higher than the mean SRS value of Teófilo Otoni. In CAPS II shows that Ouro Verde de Minas interns on average 10 inhabitants per year, while the average of Teófilo Otoni is 02 hospitalizations. It was concluded that around 60% of the municipalities of the SRS of Teófilo Otoni there was an increase in the number of hospitalizations due to mental disorders, and projections of the number of hospitalizations for the coming years were presented.